2020
DOI: 10.1038/s41598-020-70110-1
|View full text |Cite
|
Sign up to set email alerts
|

RNA polymerase II subunit D is essential for zebrafish development

Abstract: DNA-directed RNA polymerase II (pol II) is composed of ten core and two dissociable subunits. The dissociable subcomplex is a heterodimer of Rpb4/Polr2d and Rpb7/Polr2g, which are encoded by RPB4/polr2d and RPB7/polr2g genes, respectively. Functional studies of Rpb4/Polr2d in yeast have revealed that Rpb4 plays a role primarily in pol II-mediated RNA synthesis and partly in various mRNA regulations including pre-mRNA splicing, nuclear export of mRNAs and decay of mRNAs. Although Rpb4 is evolutionally highly co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…This result illustrated the conservation of the nine genes in HCC patients. Among the nine PRGs, four of them ( EZH2 , POLR2G , POLR2L , and PRC1 ) also regulate gene expression through other pathways, such as histone methyltransferase and transcription regulation ( Acker et al, 1996 ; Maeta et al, 2020 ; Xue et al, 2021 ). In our study, we found that the increased expression of those genes also correlated with higher progressive tumor grades and advanced metastatic stages.…”
Section: Discussionmentioning
confidence: 99%
“…This result illustrated the conservation of the nine genes in HCC patients. Among the nine PRGs, four of them ( EZH2 , POLR2G , POLR2L , and PRC1 ) also regulate gene expression through other pathways, such as histone methyltransferase and transcription regulation ( Acker et al, 1996 ; Maeta et al, 2020 ; Xue et al, 2021 ). In our study, we found that the increased expression of those genes also correlated with higher progressive tumor grades and advanced metastatic stages.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we also identified proteins with known roles regulating chromatin compaction and transcription, which belonged to categories of (i) DNA helicase activity, (ii) single-stranded DNA binding, (iii) promoter-specific chromatin binding proteins, (iv) adenosine triphosphate–dependent activity on DNA or RNA, (v) transcriptional co-regulators or co-activator activity, (vi) transcription factor binding, and (vii) chromatin binding enriched. Particularly, we observed proteins such as MED12L and POLR2D, which form part of the RNA polymerase II transcription complex and are directly involved with transcription ( 41 45 ). We also observed proteins such as the histone variant MACROH2A.1 and the chromodomain protein CBX1 (also known as HP1-β) both of which have known functions in condensation and decondensation of chromatin ( 46 48 ).…”
Section: Resultsmentioning
confidence: 99%
“…According to Maeta et al, mutations in polr2d severely impaired the expression of zygotic and housekeeping genes in zebrafish. 71 Importantly, all of the polr2d/RPB4-mutant organisms were lethal, except for RPB4 mutant S. cerevisiae, which could grow at a normal temperature. 72 The high lethality of affected cases can be attributed to a low detected mutation rate in POLR genes (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the importance of POLR genes, few mutations have been reported in vertebrates. According to Maeta et al, mutations in polr2d severely impaired the expression of zygotic and housekeeping genes in zebrafish 71 . Importantly, all of the polr2d/RPB4 ‐mutant organisms were lethal, except for RPB4 mutant S .…”
Section: Discussionmentioning
confidence: 99%